PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TYPE PICTURE AND PICTURE UNTUK MENINGKATKAN AKHLAKUL KHARIMAH DAN PRESTASI BELAJAR SISWA (Studi Pada Mata Pelajaran Pendidikan Agama Islam Kelas II SD Negeri 36 Pagar Alam) - Suzie Hery Sandy (DIADIK, 2021)
The purpose of this study (1) Application of Cooperative Learning Model Types of Pictures and Images to improve the students' moral character in the second grade Islamic Religious Education subject at SD Negeri 36 Pagar Alam. (2) Application of the Cooperative Learning Model Types of Pictures and Images to improve student achievement in the second grade Islamic Religious Education subject at SD Negeri 36 Pagar Alam. (3) The effectiveness of the application of the cooperative learning model types of pictures and pictures when compared to conventional learning methods. The population of this study were students of class II SD Negeri 36 Pagar Alam who were taken in 18 people, grade II students of SD Negeri I3 Pagar Alam were included in 40 people with a total of 58 people, from different schools the population was insufficient for the total sampling, namely for the control class. and the experimental class, but the school which is the experimental class and the control class is geographically located not so far from the school that is the research subject, in one sub-district about 10 minutes from the research subject class school. Sampling is done by total sampling, which is determined by taking the entire population into a sample. The research sample that acts as an action class is class IIC SDN 36 Pagar Alam which is assessed by 18 students, the experimental class research is class II which can be determined by 20 students from SD Negeri 13 Pagar Alam, for the control class is class II B which corresponds to 20 students who is at SD Negeri 13 Pagar Alam. Technique data using observation sheets and tests. The result of this research is learning with the application of the Cooperative Learning Model Types of Pictures and Images that can improve students' moral values in learning, especially in the subject of Islamic Religious Education